2019
DOI: 10.3390/sym11080956
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption Load Forecasting Using a Level-Based Random Forest Classifier

Abstract: Energy consumers may not know whether their next-hour forecasted load is either high or low based on the actual value predicted from their historical data. A conventional method of level prediction with a pattern recognition approach was performed by first predicting the actual numerical values using typical pattern-based regression models, hen classifying them into pattern levels (e.g., low, average, and high). A proposed prediction with pattern recognition scheme was developed to directly predict the desired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The proposed approach consists of converting the dataset values into levels during the pre-processing phase, instead of the post-processing phase, allowing the direct prediction of the desired levels using simpler classifier models without undergoing regression. Using a 12-month dataset of a large hypermarket, consisting in hourly energy consumption and temperature, as well, as 10-time cross-validation, it was concluded that the proposed approach performs better for all tests done, which were of 3, 5, and 7 levels, then the conventional way, however, the performance of the conventional classifier was also concluded to be able to approach the proposed method in terms of classification accuracy at the expense of computation time (Chen et al, 2019).…”
Section: Related Workmentioning
confidence: 95%
See 2 more Smart Citations
“…The proposed approach consists of converting the dataset values into levels during the pre-processing phase, instead of the post-processing phase, allowing the direct prediction of the desired levels using simpler classifier models without undergoing regression. Using a 12-month dataset of a large hypermarket, consisting in hourly energy consumption and temperature, as well, as 10-time cross-validation, it was concluded that the proposed approach performs better for all tests done, which were of 3, 5, and 7 levels, then the conventional way, however, the performance of the conventional classifier was also concluded to be able to approach the proposed method in terms of classification accuracy at the expense of computation time (Chen et al, 2019).…”
Section: Related Workmentioning
confidence: 95%
“…Chen, Piedad Jr., and Kuo, in 2019, also used a Random Forest for energy consumption load forecasting (Chen et al, 2019). In this approach, the authors propose the use of a level-based methodology, contrary to the conventional value-based methodology approach, that works by training the model with the pre-processed dataset values and then converting the results into consumer-preferred levels (e.g., low, average, high).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in [8], [31]- [34] the authors used datasets of eighteen months to two years duration for developing forecasting models. Data of one year was used in [6], [35]- [37] while three years data was used in [38]. In this study, a time series data of hourly electricity consumption of Muzaffarabad city in kilowatt-hour (KWh), across the time period from 1 st January 2014 to 31 st December 2015 (two years) is used.…”
Section: Datasetsmentioning
confidence: 99%
“…Chen et al reported "Energy Consumption Load Forecasting Using a Level-Based Random Forest Classifier" [19]. In this study, a conventional method of level prediction with a pattern recognition approach was performed by first predicting the actual numerical values using typical pattern-based regression models, and then classifying them into pattern levels (e.g., low, average, and high).…”
Section: Lan Et Al Reported "Symmetric Modeling Of Communication Effectiveness and Satisfactionmentioning
confidence: 99%